Research progress of vagus nerve stimulation in the treatment of epilepsy. (19th August 2019) - Fan, Jing‐Jing; Shan, Wei; Wu, Jian‐Ping; Wang, Qun
Abstract: The International League Against Epilepsy (ILAE) defined drug‐resistant epilepsy (DRE) that epilepsy seizure symptoms cannot be controlled with two well‐tolerated and appropriately chosen antiepileptic drugs, whether they are given as monotherapy or in combination. According to the WHO reports, there is about 30%‐40% of epilepsy patients belong to DRE. These patients need some treatments other than drugs, such as epilepsy surgery, and neuromodulation treatment. Traditional surgical approaches may be limited by the patient's clinical status, pathological tissue location, or overall prognosis. Thus, neuromodulation is an alternative choice to control their symptoms. Vagus nerve stimulation (VNS) is one of the neuromodulation methods clinically, which have been approved by the Food and Drug Administration (FDA). In this review, we systematically describe the clinical application, clinical effects, possible antiepileptic mechanisms, and future research directions of VNS for epilepsy.